Persepsi Masyarakat Terhadap Pengangkutan Sampah di Kota Ternate - Amelia, Risky; Rauf, Ichsan; Gaus, Abdul; Sultan Amir, Mufti; Pasongli, Hernita (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
The enviroment is something that is important for living things, especially humans. The enviroment is used by humans to meet the needs of life, if it does not take care of the enviroment properly it will cause enviromental problems. There are many environmental problems, one of which is the waste problem. The problem of waste is a problem that often occurs in urban areas, one of which is in the city of Ternate. The Ternate City Government needs tochoose the right solution to overcome the problems that occur due to waste, but before making a solution it is necessary to know how the public’s perception of waste transportation in Ternate City is. The research method is descriptive quantitative using a questionnaire distributed to respondents as a research instrument. The sampling technique used in this research is random sampling with a sample of 400 respondents in four districts in Ternate City. The sample of each sub-district amounted to 100 respondents. Data analysis using interpreted percentages. The results showed that the public’s perception of waste transportation in Ternate City was good.